Study of adsorption of cadmium ions from solutions on natural and modifi ed diatomites - Boriskov, Dmitry E.; Efremova, Sania Yu.; Komarova, Nadezhda А. (Известия Саратовского университета. Новая серия: Серия Химия. Биология. Экология, 2023)
The search for new technologies for the purification of natural and waste water does not lose its relevance. Biologically, heavy metals are among the most dangerous pollutants. The highest toxicity among them has cadmium, causing serious environmental problems during technogenic pollution of the aquatic environment, and its extraction is an urgent task. The analysis of foreign studies on the extraction of cadmium ions is carried out. The adsorption of cadmium has been studied by many authors and described in many works on kaolin oxides / iron hydroxides, in contrast to siliceous rocks. In this work, the use of the sorption method is proposed for the purification of wastewater from ions of heavy metals. The aim was to study the sorption activity of diatomite in relation to cadmium ions. The studies have been carried out under static conditions. The processes of physicochemical modification of diatomite for the extraction of cadmium ions from aqueous solutions have been investigated. The influence of time and pH on the value of sorption has been studied. The optimal conditions for sorption extraction have been determined. Adsorption isotherms have been constructed, and quantitative characteristics of the values of adsorption of cadmium ions on the surface of modified sorbents have been obtained. The fundamental possibility of using diatomites for the purification of cadmium-containing wastewater has been assessed. Based on the data obtained, it can be concluded that acid activation does not promote adsorption (even negative adsorption is observed), which confirms the mobility of cadmium in the low pH region, it can be assumed that only an increase in alkalinity to the possibility of formation of hydroxocadmium (CdOH)+. Thermal, shows stable adsorption in relation to Cd+2, which suggests the possibility of using such activation of cadmium diatomite and other metals, that is, with complex pollution.